Estudo sobre o auxílio Bolsa Formação Profissional no Instituto Federal do Tocantins como benefício de assistência estudantil - Oliveira, Adilvana Gomes (Universidade Federal do Tocantins, 2021)
This study sets out to examine how effective the aid contributor, as the benefit of lowincome student assistance the IFTO-Campus of applause. Taking into account that the student assistance program is run by the institution since your creation in the year 2005. However, by observing the ways of obtaining the aid, it was realized that this is insufficient to meet the real needs of the poor student who studies at the Institute in question. Yes, not all students applying for aid can be selected to receive the scholarship. While other students even getting the aid eventually give up studies because of some factors that do not were part of the research. But, if the help unveil Valley developer is enough to meet all the needs of the students receiving the scholarship, despite the difficulties they present more chances to finish the degree course successfully. To better understand the analysis of aid contributor, as part of the benefit of student assistance in the IFTO – Campus de Palmas, the research was coordinated from three main themes, which are directly connected to the subject. The first, "higher education in Brazil and the Student Assistance policy", presents the history of higher education in Brazil, since the Jesuit phase until the contemporary phase, with advances and setbacks with respect to the main legislation Brazilian educational throughout the ages; The second, "the Student Assistance in the IFTO – Campus de Palmas," features the Institute and the practice of student assistance, adopts from the regulatory policies of aid provided to students; The third, "the situation of education in Brazil and the field of the social worker", makes an analysis of the education as a social right and the relevance of the role of the social worker as articulator in the implementation of education policies for social inclusion. To examine some of the factors that affect negatively or positively to the completion of the permanence of students in undergraduate courses, financial aid can be counted as a means for the student to successfully reach your vocational training.